Empty‐State Band Mapping Using Momentum‐Resolved Secondary Electron Emission. (15th October 2020) - Wan, Gary; Croot, Alex; Fox, Neil A.; Cattelan, Mattia
Abstract: Material band structures of occupied electronic states are obtainable using conventional angle‐resolved photoemission experiments, leaving the unoccupied states far less explored. Here, an alternative approach is built on and expanded to investigate thermalized photoelectrons emitted from crystal surfaces. A model for electron emission is constructed and reveals the material unoccupied state band structure. Potentially applicable to any material and independent from the secondary electron generation mechanism, it is demonstrated on diamond and copper using different light sources. Moreover, the diamond indirect band gap is directly observed and the transverse effective mass at the conduction band minimum can be experimentally obtained, m t = (0.21 ± 0.015) m e . This offers a convenient path for angle‐resolved photoemission data interpretation and empty‐state information extraction. Abstract : Secondary electron emission can be exploited to gain information on unoccupied band structure states. Electron surface‐parallel momentum is conserved during emission while the perpendicular momentum is unrestricted, showing an abundance of states. This technique works for most crystals, while in certain cases can be used to determine electron effective mass.